Comparison between older adults who are homebound and nonhomebound - McNulty, Martina Cooper, author; Lehmann, Jean, advisor; Fisher, Anne, advisor (Colorado State University. Libraries, 2003)
The objective of this study was to investigate the differences in activities of daily living (ADL) ability, level of satisfaction with ADL performance, and home safety among older adults who were chronically homebound and two groups of older adults who were nonhomebound: those who were independent and those who needed assistance. The second objective was to examine the influence of three psychosocial variables (i.e., self-identification of ADL problems, perception of role incumbency, and the presence of depressive symptoms) on participants' ADL ability, level of satisfaction with ADL performance, and home safety. The results of three analyses of variance (ANOVA) revealed that participants who were chronically homebound (n = 20) had significantly lower ADL motor ability, ADL process ability, and level of satisfaction with ADL performance compared to those who were nonhomebound and independent with performing ADL (n = 10). However, these variables did not differ significantly between participants who were nonhomebound and had assistance with ADL and participants who were homebound. The mean home safety ability measure for the nonhomebound with assistance group was significantly greater than the homebound group, and significantly less than the nonhomebound independent group. Low to moderate relationships (r = -.36 to -.50) were found between the number of self-identified ADL problems and the dependent variables of ADL motor ability, ADL process ability, level of satisfaction with ADL performance, and home safety. Low relationships (r = .25 to .35) were found between the number of perceived roles currently occupied and the same dependent variables. Low relationships (r = -.33 to -.41) were also found between the number of depressive symptoms and the dependent variables. A moderate canonical correlation was found (r - .58) between (a) the three psychosocial variables studied, and (b) the dependent variable set comprised of ADL motor ability, ADL process ability, and home safety ability. The findings support the need for occupational therapists to provide services for older adults who have ADL limitations regardless of their homebound status. Further research is needed to evaluate the complex relationships between psychosocial variables and older adults' ADL and home safety ability.
Keywords: rehabilitation; occupational therapy; comparative analysis; older people; physical therapy